(untitled) (Journal of the College of Basic Education, 2022)
The purpose of this paper is to present a fiber optic sensors intrusion system based on the monitoring of the mode distribution change (speckle pattern) in a multimode optical fiber. Detection of vibrations and their parameters is possible through observation the variation in the output speckle pattern from the multimode optical fiber. The implementation of sensor consists of a multimode fiber which is isolated and sensitive to vibration, a CCD camera beam profile, and a computer with specific algorithms for signal processing. The intrusion system is simple, inexpensive and can be implemented to measure vibrations and movement in the protection sites.